2023
DOI: 10.1038/s42003-023-04747-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct transcriptomic and epigenomic modalities underpin human memory T cell subsets and their activation potential

Abstract: Human memory T cells (MTC) are poised to rapidly respond to antigen re-exposure. Here, we derived the transcriptional and epigenetic programs of resting and ex vivo activated, circulating CD4+ and CD8+ MTC subsets. A progressive gradient of gene expression from naïve to TCM to TEM is observed, which is accompanied by corresponding changes in chromatin accessibility. Transcriptional changes suggest adaptations of metabolism that are reflected in altered metabolic capacity. Other differences involve regulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 85 publications
(94 reference statements)
1
7
0
Order By: Relevance
“…Our analysis, utilizing the previously identified naïve and effector gene modules (GEP3-6; Fig 1K, Supplementary Tables VIII-XII), indicated that each of the investigated cell types could be found within these identified gene programs, albeit with varying proportions for each cell type (Fig 4C, D). To provide further context and understanding of these gene modules, we computed overlap scores and statistically assessed their enrichment with literature-derived signatures (Cano-Gamez et al, 2020; Poon et al, 2023; Rose et al, 2023; Terekhova et al, 2023). Subsequently, we scored the joint signature-GEP interactions in our dataset (Supplementary Fig 9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis, utilizing the previously identified naïve and effector gene modules (GEP3-6; Fig 1K, Supplementary Tables VIII-XII), indicated that each of the investigated cell types could be found within these identified gene programs, albeit with varying proportions for each cell type (Fig 4C, D). To provide further context and understanding of these gene modules, we computed overlap scores and statistically assessed their enrichment with literature-derived signatures (Cano-Gamez et al, 2020; Poon et al, 2023; Rose et al, 2023; Terekhova et al, 2023). Subsequently, we scored the joint signature-GEP interactions in our dataset (Supplementary Fig 9).…”
Section: Resultsmentioning
confidence: 99%
“…We obtained gene signatures identified from (1) differential expression (DE) analysis from bulk RNAseq between sorted naïve, T cm , T em CD4 + and CD8 + T cell populations by Rose et al . (Rose et al ., 2023); (2) DE genes between cell clusters defined from scRNAseq of naïve and memory CD4 + T cells isolated from PBMCs by Cano-Gamez et al . (Cano-Gamez et al ., 2020); (3) DE genes between cell clusters defined from scRNAseq of blood immune cells by Terekhova et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites derived from glucose metabolism, such as acetyl-CoA and α-ketoglutarate, serve as pivotal substrates for epigenetic modifications and gene expression regulation 40 . These metabolic intermediates influence chromatin accessibility and transcriptional programs, ultimately moulding T-cell differentiation into distinct effector subsets 41 . The comprehensive understanding of the intricate interplay between glucose metabolism and T-cell biology holds therapeutic implications.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies used gene chromatin accessibility profiles to supplement genes' expression profiles for defining T cell subpopulations. [85][86][87] . We adopted the same strategy.…”
Section: Sifinet Accurately Annotated Cd8 T Cells and Identified Long...mentioning
confidence: 99%